Improved techniques for assayinq protein concentration in geminating Neurospora conidia. - R. L. Christensen; D. Wolens; J. C. Schmit (Fungal Genetics Reports, 1980)
Improved techniques for assayinq protein concentration in geminating Neurospora conidia.